High-Temperature, High-Shear Oil Viscosity: Measurement and Relationship to Engine Operation 1989
DOI: 10.1520/stp22999s
|View full text |Cite
|
Sign up to set email alerts
|

Development of ASTM Standard Test Methods for Measuring Engine Oil Viscosity Using Rotational Viscometers at High-Temperature and High-Shear Rates

Abstract: Two ASTM standards have been developed for the measurement of engine oil viscosity at high temperature (150°C) and high shear rate (106 s-1) using rotational viscometers. Both methods resulted from significant international participation at the working group level. One test method resulted from work done primarily within ASTM Committee D-2, Subcommittee 7, using the tapered bearing simulator. The other resulted from work done within the Co-ordinating European Council (CEC) using the Ravenfield viscometer, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This meant that the shear thinning behaviour of VM solutions could not be fully explored. Typical flow curves of engine oils up to 10 6 s −1 can be found in [8][9][10][11]. This limitation has recently been addressed by the development of the PCS ultrashear viscometer (USV) that is able to reach 10 7 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…This meant that the shear thinning behaviour of VM solutions could not be fully explored. Typical flow curves of engine oils up to 10 6 s −1 can be found in [8][9][10][11]. This limitation has recently been addressed by the development of the PCS ultrashear viscometer (USV) that is able to reach 10 7 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Viscometers based on this geometry have been employed since the 1980s to measure the viscosity of lubricants up to 10 6 s -1 [55,56] and, more recently, up to 10 7 s -1 [57]. In a recent study, it was shown that the application of shear rates above 10 6 s -1 in a concentric cylinder viscometer results in significant permanent viscosity loss of polymer solutions and that this can be used to compare the shear stability of VMs [58].…”
Section: Introductionmentioning
confidence: 99%